Anomalous re-ordering of Fe3Al disordered by high pressure torsion deformation. (November 2018) - Gammer, C.; Mangler, C.; Karnthaler, H.P.; Rentenberger, C.
Abstract: Severe plastic deformation of bulk DO3 ordered Fe-30 at.%Al was carried out using high pressure torsion to make a chemically disordered nanocrystalline alloy. To achieve re-ordering the alloy was heated to 250, 370 and 500 °C. Transmission electron microscopy investigations reveal that in contrast to the phase diagram B2 ordering occurs at low temperatures. Upon further heating, after the B2 order is already well restored, nanosized DO3 ordered domains grow within large B2 ordered regions. It is proposed that the anomalous re-ordering is triggered by deformation-induced vacancies and other defects leading to the formation of the high-temperature B2 ordered phase. Graphical abstract: